1996
DOI: 10.1001/archinte.156.4.433
|View full text |Cite
|
Sign up to set email alerts
|

Stenotrophomonas (Xanthomonas) maltophilia urinary tract infection. A disease that is usually severe and complicated

Abstract: Stenotrophomonas maltophilia urinary tract infection is usually associated with a severe clinical course. Risk factors for urinary colonization by this organism include hospitalization, urinary catheterization, and administration of inactive antibiotics. Risk factors for urinary tract infection include neutropenia and urinary structural abnormalities. In the presence of these risk factors, treatment of S maltophilia should be considered in patients with urinary colonization by the organism or in those with nos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
32
0
1

Year Published

2000
2000
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 11 publications
1
32
0
1
Order By: Relevance
“…3,4 Infection with this pathogen commonly manifests as bacteremia, [1][2][3][4][5][6][7][8][9][10] although it can cause a wide spectrum of other infections as well. [11][12][13][14][15][16][17][18][19][20][21] Several studies have identified major risk factors for the infection, including neutropenia, prolonged hospitalization, previous antibiotic use, steroid use, mechanical ventilator support, and the use of medical devices such as prosthetic heart valves, urinary catheters, and indwelling central venous catheters (CVCs). [1][2][3][4][5][6][7][8][9][10]17,18 However, to our knowledge very little information is available regarding how often CVCs are the source of the bacteremia.…”
mentioning
confidence: 99%
“…3,4 Infection with this pathogen commonly manifests as bacteremia, [1][2][3][4][5][6][7][8][9][10] although it can cause a wide spectrum of other infections as well. [11][12][13][14][15][16][17][18][19][20][21] Several studies have identified major risk factors for the infection, including neutropenia, prolonged hospitalization, previous antibiotic use, steroid use, mechanical ventilator support, and the use of medical devices such as prosthetic heart valves, urinary catheters, and indwelling central venous catheters (CVCs). [1][2][3][4][5][6][7][8][9][10]17,18 However, to our knowledge very little information is available regarding how often CVCs are the source of the bacteremia.…”
mentioning
confidence: 99%
“…It has been found in the environment as a growth-promoting agent in the rhizospheres of plants, as well as in soil, water, sediment, sewage, frozen foods, and some other habitats (3,8,14,20,23,25). More importantly, S. maltophilia is increasingly prevalent in hospitals as an opportunistic human pathogen causing nosocomial infections in immunocompromised individuals and involved in postoperative infections, the infections of urinary tracts and respiratory tracts, and other disease syndromes (15,20,34,40). This organism was reported to be the second most frequently isolated nosocomial bacterium after Pseudomonas aeruginosa, and its infections have a growing clinical importance (43).…”
mentioning
confidence: 99%
“…The major risk factors for S. maltophilia infection include long-term hospitalization, previous antimicrobial therapy, fungal infections, catheterization, and mechanical ventilation. S. maltophilia infection can cause bacteremia, endocarditis, pneumonia, mastoiditis, peritonitis, meningitis, or infections of the eyes, bones, joints, urinary tract, soft tissues, and wounds (4,7,10,19,21,29,30,39). The management of infections caused by S. maltophilia is particularly difficult because of its inherent resistance to many currently available broad-spectrum antibiotics (5,10,11,20,22,34).…”
mentioning
confidence: 99%